Does the Position of the Third Molar Have an Influence on the Location of Mandibular Fractures? - Julio Cesar C Moretti; Rubens Camino Junior; Celso F Palmieri Jr; Joao Gualberto C Luz (Wolters Kluwer Medknow Publications, 2022)
Introduction: This study evaluated the possible influence of the lower third molar and its position on the location of fractures in all mandibular regions. Methods: Computed tomography scans of patients with mandibular fractures in any region seen between August 2018 and July 2019 were evaluated. The presence and classification of third molars according to their vertical and horizontal positions and angulations were analyzed. Data were analyzed using the chi-square test, tree algorithm, and random forest model. Results: A total of 49 patients with mandibular fractures were seen and 40 patients (80% men), with a mean age of 33.4 years, were included. There was no correlation between fracture location and the vertical (P = 0.93) and horizontal (P = 0.76) Pell and Gregory classifications. There was a statistically significant relationship between fracture location and the Winter angulation classification (P = 0.01). Conclusion: Relative to the possible influence of lower third molars and their position on the location of mandibular fractures in all mandibular regions, only the angulation of the third molar had an influence. There was no correlation between the presence and the classifications of third molar impaction.